Young Learner’s Home Literacy Habit and The Environmental Support: A Study of A High Achievement Young Learner - Irene Rosalina; Inayatus Sholihah (SELING: Jurnal Program Studi PGRA, 2018)
Home literacy environment gives a beneficial support to a young child. This study elaborates how the literacy habit and the environmental support of a high achievement young learner in Tapas Mojokerto. This study applied a descriptive qualitative study that proposed the data analysis descriptively. The data triangulation used to validate the finding, so the observation at home, a cchecklist of a literacy and parent interview were used to gain the data. Furthermore, the finding showed that the score of the checklist done by the mother of the subject was 33 from all 37 true score, where it can be stated from the description that the literacy practice at home has the most supportive foundations in our participant’s home. Every checklist sessions on each part of the questions was answered with a high score. It means that the home literacy habit and the environmental support were rich and high. The habitual literacy activity done by the subject is define an ORIM framework application.